DIGITAL MARKETING TOURISM DESTINIATION PARI CITY VILLAGE PANTAI CERMIN DISTRICT SERDANG BEDAGAI REGENCY - Ritonga, Husni Muharram; Daulay, Muhammad Toyib; Erwansyah, Erwansyah (Proceeding International Conference of Science Technology and Social Humanities, 2023)
Digital marketing in the current era is very important, especially in marketing a product, especially tourism. This study aims to help rural communities to continue to do tourism marketing with a digital concept. The location of the study was Pari City Village, Pantai Cermin District, Serdang Bedagai Regency. This research used a descriptive qualitative research method with a total of 15 informants. The results of the study explained; 1) the need to carry out sustainable tourism development, 2) utilize information technology as a digital marketing effort, 3) evaluate the Village website so that more information is needed by the community, 4) promotion of village tourism with social media, 5) the concept of atention, interest, desire, action (AIDA) and 6) branding village tourism.